Causes and Consequences of Globally Warm Climates in the Early Paleogene 2003
DOI: 10.1130/0-8137-2369-8.239
|View full text |Cite
|
Sign up to set email alerts
|

Early Paleogene transgressions: Stratigraphical and sedimentological evidence from the northern Peri-Tethys

Abstract: Our study in lithologically diverse lower Paleogene deposits of the former southern USSR and West Siberia resolves three sedimentary provinces: (i) Southern (Crimea-Caucasus and Central Asia), dominated by biogenic calcareous sediments of the deepest basinal portions; (ii) Transitional (southern Russian craton and Turan plate), displaying calcareous and siliceous clayey deposits; and (iii) Northern (central Russian craton and West Siberian plate), showing biogenic siliceous and terrigenoussiliceous sediments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…The 2nd Paleogene sea incursion in the Tarim Basin appears also coeval with the fluctuations in the Siberian Sea where a transgression during the Lutetian (starting at ca. 47 Ma) is reported by Radionova et al () (Figure ). During this interval, an increase is indicated in the global sea level reconstruction curve of Haq et al ().…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The 2nd Paleogene sea incursion in the Tarim Basin appears also coeval with the fluctuations in the Siberian Sea where a transgression during the Lutetian (starting at ca. 47 Ma) is reported by Radionova et al () (Figure ). During this interval, an increase is indicated in the global sea level reconstruction curve of Haq et al ().…”
Section: Discussionsupporting
confidence: 58%
“…Regional coastlines and depositional environments during the maximum Paleogene sea advances and retreats were drawn based on the results of this study and integrated with existing literature. The updated palaeo‐reconstructions of Poblete et al () integrating continental reference points, palaeotopography and shorelines were updated with data from the Darius project (Barrier et al, ), Peri‐Tethys atlas (Dercourt et al, ), the compilation of Bosboom et al () and palaeogeographical changes in the Turgai Strait and West Siberian Sea were drawn based on Radionova et al (), Akhmetiev and Beniamovski (), Akhmetiev et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tectonic reconstructions of the early Paleogene Arctic [Lawver et al, 2002;Thiede and Myhre, 1996] have suggested that deepwater exchange between the Arctic and the world ocean was much more restricted than it is today. There was probably a shallow intermittent connection between Tethys and the Arctic via the western Siberian seaway (Turgay Strait [Radionova et al, 2003]) through the end of early Eocene time (Figure 2), and possibly into the early part of the middle Eocene [Onodera et al, 2008]. The water depth of this connection is unknown; however, with the lack of any significant land ice during the warmest part of the Eocene, sea level may have been 70-80 m higher than it is today [Miller et al, 2005a].…”
Section: Paleo-arctic Ocean Basinmentioning
confidence: 99%
“…2013.775366 Horizon is a major disoxic level originating after the Lutetian/Bartonian transgression, which has been assigned to the CP14 nannoplankton zone and Subbotina turkmenica foraminiferal zone (40-39 Ma; Radionova et al 2003). The indeterminate gempylid taxon from the Campanian (79.66 Ma) Coffee Sand Formation, Griffin Sandpit, Mississippi (Nolf & Stringer 1996) is used to establish an upper boundary.…”
Section: Supplementary Materialsmentioning
confidence: 99%